A computational study of carrier lifetime, doping concentration, and thickness of window layer for GaAs solar cell based on Al2O3 antireflection layer. (1st March 2022) - Shah, Deb Kumar; KC, Devendra; Parajuli, D.; Akhtar, M. Shaheer; Kim, Chong Yeal; Yang, O-Bong
Highlights: A computational study was done to optimize high performance GaAs solar cells with Al2 O3 ARC. Input parameters such as carrier lifetime, doping concentration, energy bandgap, thickness were used. GaAs solar cells with Al2 O3 ARC achieved high efficiency of 24.60% at 30 nm CdS layer. Doping concentration and carrier lifetime found to be crucial for solar cells. Abstract: This paper reports on the computational study to investigate the high-performance gallium arsenide (GaAs) solar cells based on the Al2 O3 antireflection coating (ARC) layer by optimizing the carrier lifetime, doping concentration, energy bandgap, thickness of window and absorber layers. In this simulation, the parameters like GaAs as an absorber layer, CdS as a window layer, and fixed thickness of the Al2 O3 ARC layer were selected for performing the personal computer one dimensional (PC1D) simulation. As compared to GaAs solar cell with no ARC layer, GaAs solar cell with Al2 O3 ARC layer (90 nm) presented the high power conversion efficiency (PCE) of 24.60% at absorber thickness 6 μm and 30 nm for window layer. The optimized values of carrier lifetime and doping concentration for high PCE were found to be 100 μs and 1 × 10 17 cm −3 for both absorber and window layers, respectively. The Voc, PCE, and fill factor (FF) values gradually increased with the increase of carrier lifetime and doping concentration of the CdS window layer. At optimized parameters, the highest value of Isc = 3.11 A, Voc = 0.884 V and PCE = 24.60% were achieved by GaAs solar cells with Al2 O3 ARC layer. This study proves that optimization of CdS window layer through carrier lifetime, thickness, doping concentrations, and bandgap, etc. would make the crucial component to manufacture cost-effective, high-performance GaAs solar cells based on Al2 O3 ARC layer.